Intra-Industry Trade in Indonesia: A Case of the Textile and Textile Product Industry - Revinda Yonita Permata Sari; Lilis Yuliati; Siti Komariyah (Journal of International Business, Economics and Entrepreneurship, 2019)
Trade is one of the instruments driving the economy that has a great dependence on global dynamics. Several trade policies in Indonesia have been carried out to encourage the performance of export imports through various collaborations with Indonesia's largest trading partner countries such as China. The trade intensity that occurs in both countries is certainly expected to have an impact on the economy. This study aims to see the intra-industry intensity of trade, especially in the textile goods sector between Indonesia and China. The result shows that Intra-textile textile trade intensity between Indonesia and China, from 2000-2013 based on the ISIC 321 category (textile industry) obtained by Indonesia and China intra-industry trade, because the overall intra-industry trade index is 53.9%. Suggestion to the The government is expected to be able to boost the performance of exports and consumption of the domestic community, because so far Indonesia's economic growth has been driven more by the performance of exports and household consumption which is still quite strong; Policies regarding investment licensing must be further simplified and there is a guarantee of the availability of energy supplies for the textile industry machinery. The government must also try to increase investment in the textile industry sector especially to modernize old or worn machines so that the textile industry can expand production.